2021
DOI: 10.3389/fcell.2021.694633
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analyses Identify a Prognostic Autophagy-Related Long Non-coding RNA Signature Associated With Immune Microenvironment in Diffuse Gliomas

Abstract: BackgroundAutophagy and long non-coding RNA (lncRNA) play a critical role in tumor progression and microenvironment. However, the role of autophagy-related lncRNAs (ARLs) in glioma microenvironment remains unclear.MethodsA total of 988 diffuse glioma samples were extracted from TCGA and CGGA databases. Consensus clustering was applied to reveal different subgroups of diffuse gliomas. Kaplan-Meier analysis was used to evaluate survival differences between groups. The infiltration of immune cells was estimated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…Through mining the publicly available transcriptome sequencing data by bioinformatics analysis, many studies have constructed lncRNA signatures that predict cancer prognosis, including lung adenocarcinoma ( 19 ), gastric cancer ( 20 ), breast cancer ( 21 ), bladder urothelial carcinoma ( 22 ), hepatocellular carcinoma ( 23 ), and diffuse gliomas ( 24 ). In our study, we downloaded and integrated the gene expression data and clinical information of patients with COAD from the TCGA database, and COAD patients were divided into a training cohort and validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Through mining the publicly available transcriptome sequencing data by bioinformatics analysis, many studies have constructed lncRNA signatures that predict cancer prognosis, including lung adenocarcinoma ( 19 ), gastric cancer ( 20 ), breast cancer ( 21 ), bladder urothelial carcinoma ( 22 ), hepatocellular carcinoma ( 23 ), and diffuse gliomas ( 24 ). In our study, we downloaded and integrated the gene expression data and clinical information of patients with COAD from the TCGA database, and COAD patients were divided into a training cohort and validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, integrating multiple gene biomarkers into a single signature was adopted because the prediction accuracy of the signature can be enhanced compared to a single biomarker [ 48 ]. Previous studies have reported that this biomarker signature of gliomas, such as the autophagy-related signature [ 49 , 50 ], ferroptosis-related signature [ 51 ], and mesenchymal-related signature [ 52 ], has shown strong prognostic power. In addition, although an ERS-related signature has been reported, it is entirely different from ours, and too many genes to make up the signature results inconvenient and impractical in clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…As is known, the occurrence and progression of many human cancers are related to cancer hallmarks such as immune response, and immunotherapy has curative effects on certain cancers (27)(28)(29). It has been reported that immune cells such as CD8 + T cells, monocytes, memory CD4 + T cells, and mast cells are significantly related to the OS of UM patients (30).…”
Section: Discussionmentioning
confidence: 99%